Case Report: An azygos vein aneurysm with dysphagia assisted diagnosis by esophageal endoscopic ultrasonography - Guo, Xueyan; Xu, Yuanhang; Cao, Yanfei; Jin, Yan (Frontiers in Oncology, 2025)
BackgroundAzygos vein aneurysm (AVA) is a rare thoracic pathology that is frequently misdiagnosed. While contrast-enhanced chest computed tomography (CT) or magnetic resonance imaging (MRI) can delineate AVA location and size, these techniques lack the capability for dynamic real-time assessment of internal architecture.Case presentationWe present a highly unusual case of a 67-year-old woman who had an isolated azygos vein aneurysm presenting with dysphagia. The mass was first found by a chest X-ray. Subsequent contrast-enhanced chest CT revealed a 3.5 × 3.74 × 1.4 cm soft-tissue mass in the posterior mediastinum, suggestive of a lymph node. In contrast, esophageal endoscopic ultrasonography (EUS) demonstrated intact esophageal mucosa with extrinsic stenosis. The dynamic observation through EUS displayed that the mass was not a lymph node but a solitary cystic lesion with no internal blood flow, and there was no communication between the posterior azygos vein and the aorta. We considered that the dysphagia was caused by the cystic lesion. Thoracoscopic surgery was finally performed, which confirmed the mass as an AVA through pathological analysis.ConclusionsEUS is one of the most effective and vital tools for the preoperative evaluation of AVA.